2017
DOI: 10.1080/14756366.2017.1404593
|View full text |Cite
|
Sign up to set email alerts
|

Symmetric molecules with 1,4-triazole moieties as potent inhibitors of tumour-associated lactate dehydrogenase-A

Abstract: A series of symmetric molecules incorporating aryl or pyridyl moieties as central core and 1,4-substituted triazoles as a side bridge was synthesised. The new compounds were investigated as lactate dehydro-genase (LDH, EC 1.1.1.27) inhibitors. The cancer associated LDHA isoform was inhibited with IC50 = 117–174 µM. Seven compounds exhibited better LDHA inhibition (IC50 117–136 µM) compared to known LDH inhibitor – galloflavin (IC50 157 µM).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Recently, molecules with 1,4-triazole moieties have been reported as potent inhibitors of LDH, but they have not been tested for anticancer activity [126].…”
Section: Possible Targets Of Lactate Metabolism and Their Potentiamentioning
confidence: 99%
“…Recently, molecules with 1,4-triazole moieties have been reported as potent inhibitors of LDH, but they have not been tested for anticancer activity [126].…”
Section: Possible Targets Of Lactate Metabolism and Their Potentiamentioning
confidence: 99%
“…It generates adequate extracellular lactate to provide a favourable microenvironment for CSCs growth and invasion[75]. Although inhibition of LDHA activity has been proposed as an approach to cancer therapy[76], a limited number of LDHA inhibitors are reported in the literature[77]. However, LDHA is transcriptionally regulated by the oncogenic transcription factor FoxM1[78], and some FoxM1 inhibitors (such as thiostrepton, troglitazone, and the FDI-6 molecule) have been reported that could indirectly lead to a reduction of LDHA[79].…”
Section: Potential Therapies Targeting Pcscsmentioning
confidence: 99%
“…The therapeutic interest for LDH inhibition prompted the development of potent, dual or selective, active-site LDH inhibitors. [24][25][26][27][28][29][30] However, despite intense efforts, pharmacological LDH inhibition struggled to translate to in vivo activity. 27,29,31,32 In fact, LDHs are usually recognized as poorly druggable targets, and different reasons can account for this.…”
Section: Introductionmentioning
confidence: 99%